Sphingolipids and Atherosclerosis: The Dual Role of Ceramide and Sphingosine-1-Phosphate - Marco Piccoli; Federica Cirillo; Andrea Ghiroldi; Paola Rota; Simona Coviello; Adriana Tarantino; Paolo La Rocca; Ivana Lavota; Pasquale Creo; Paola Signorelli; Carlo Pappone; Luigi Anastasia (Antioxidants, 2023)
Sphingolipids are bioactive molecules that play either pro- and anti-atherogenic roles in the formation and maturation of atherosclerotic plaques. Among SLs, ceramide and sphingosine-1-phosphate showed antithetic properties in regulating various molecular mechanisms and have emerged as novel potential targets for regulating the development of atherosclerosis. In particular, maintaining the balance of the so-called ceramide/S1P rheostat is important to prevent the occurrence of endothelial dysfunction, which is the trigger for the entire atherosclerotic process and is strongly associated with increased oxidative stress. In addition, these two sphingolipids, together with many other sphingolipid mediators, are directly involved in the progression of atherogenesis and the formation of atherosclerotic plaques by promoting the oxidation of low-density lipoproteins (LDL) and influencing the vascular smooth muscle cell phenotype. The modulation of ceramide and S1P levels may therefore allow the development of new antioxidant therapies that can prevent or at least impair the onset of atherogenesis, which would ultimately improve the quality of life of patients with coronary artery disease and significantly reduce their mortality.